Educating the Neglected Majority: The Struggle for Agricultural and Technical Education in Nineteenth-Century Ontario and Quebec - Mascio, Anthony Di (Labour / Le Travail, 2017)
This article reviews the book, "Educating the Neglected Majority: The Struggle for Agricultural and Technical Education in Nineteenth-Century Ontario and Quebec," by Richard A. Jarrell.